The effect of blood flow-restrictive resistance training on the risk of atherosclerotic cardiovascular disease in middle-aged patients with type 2 diabetes: a randomized controlled trial - Ma, Xiaojun; Lin, Xuandong; Zhou, Lei; Li, Wen; Yi, Qinyu; Lei, Fulian; Tang, Xuan; Ai, Yuxin; Zhan, Yating; Luo, Huanyan; Wang, Liduo; Lei, Fenfang; et al. (Frontiers in Endocrinology, 2024)
Introduction: The aim of this study was to investigate the effects of blood flow-restrictive resistance training (BFR-RT) on improving metabolic abnormalities, blood pressure (BP), obesity, and 10-year atherosclerotic cardiovascular disease (ASCVD) risk in middle-aged patients with type 2 diabetes mellitus (T2DM). Method: We conducted a parallel-group, single blind randomized controlled trial. Participants who met the inclusion criteria were randomly divided into control group, BFR-RT group and aerobic exercise (AE) group. Control group received health education and follow-up; Two exercise groups received supervised collective training for a period of six months, three times per week. AE group trained at moderate-intensity for 60 minutes each time, while BFR-RT group trained at low-intensity for 40 minutes each time. The primary outcomes were change in 10-year ASCVD risk index and level, and the secondary outcomes included changes in fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c), blood lipids, BP, and obesity level within and across the three groups at baseline, the third and sixth months of intervention. Result: Among 93 individuals (control group, n=63; AE, n=30; BFR-RT, n=32) were analyzed. At baseline, there were no significant differences in various indicators among the three groups (p>0.05). After intervention, the 10-year ASCVD risk index and risk level of both exercise groups significantly decreased (p<0.05), and the risk decrease became more pronounced over the time. In the sixth month of intervention, the 10-year ASCVD risk in the AE group decreased by 27.40%, and the risk of the BFR-RT group decreased by 26.78%. Meanwhile, apart from lipoprotein (a) and diastolic blood pressure, both exercise groups showed significant improvements in FPG, HbA1c, dyslipidemia, systolic blood pressure, and obesity indicators compared to the control group and baseline (p<0.05). There was no significant difference in various indicators between the two exercise groups (p>0.05). Conclusion: BFR-RT could reduce the 10-year ASCVD risk in middle-aged T2DM patients for by improving metabolic abnormalities, BP and obesity, and its effect was similar to that of moderate-intensity AE.